Analisis Strategi Pengembangan Sumber Daya Manusia Dalam Upaya Peningkatan Efisiensi Jam Kerja Karyawan Pada PT. PNM Mekar Syariah - Muhammad Abyan Mudhofar (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Madani Mekar Syariah National Capital (Persero) Jaten Unit Branch Office has 2,000 MSME customers divided into 110 MSME customer groups. This research aims to find out how the strategy for developing and implementing human resource development strategies is in an effort to increase the efficiency of PT employees' working hours. PNM Mekar Syariah. The type of research used is qualitative research which is descriptive analysis. The method used is the multiple linear regression analysis method. Data collection techniques use observation, interviews and questionnaires. Data analysis techniques use Descriptive Statistics, Validity Test, Reliability Test, Data Reduction, Data Presentation, Descriptive Analysis, and Drawing conclusions. Data validity techniques use Statistical Data Analysis and Hypothesis Testing. The results of this research are, holding training, holding formal education for employees, for example undergraduate level scholarships, providing regular coaching for employees, carrying out recruitment according to PT's needs. PNM Unit Jaten, gives awards to outstanding employees.